Early treatment of HIV infection in infants under two years in West Africa : accessibility, acceptability, adherence and efficacy of first-line antiretroviral treatment based on lopinavir and its determinants in the ANRS MONOD 12206 initial cohort - (:unkn) unknown (My University, 2015)
We assessed the accessibility, acceptability and efficacy at 12 months of early antiretroviraltherapy (EAT) initiated before two years of age in children HIV-infected in Côte d'Ivoire andBurkina Faso.We conducted two baseline surveys and analyzed the enrolment and therapeutic response inthe cohort recruited ahead of the MONOD ANRS 12206 trial.Despite a high prenatal HIV screening coverage of 88%, only 29% [95% CI: 27-32] exposedchildren had access to early HIV diagnosis in 2011 in Ouagadougou.In terms of knowledge, 97% of parents/caregivers of children were aware of the main route ofHIV transmission in infants. All the parents thought the child EAT was necessary, withoutreally know in what it consists.Among the 217 children referred for inclusion, 161 (74%) have initiated EAT with a medianage of 13.5 months; 70% had reached the 3/4 WHO stage, and 57% had a severe immunedeficiency. The reasons for non-inclusion were: fear or the father's refusal (48%), mortality(24%), false positives (16%), others (12%). Having already shared the child or the motherHIV status with the father and having an age ≥ 12 months were the factors associated with theinitiation of EAT.Among the 156 children who received an EAT-based lopinavir/ritonavir, 11 children died(7%), 5 were lost to follow-up (3%), 140 were followed for 12 months (90%), with 70%virological success (viral load <500 cp / mL).In 2011-2013, the challenges for improving access to EAT in HIV-infected children in WestAfrica remain. Late access is associated with a high early mortality. Nevertheless, the successrate of EAT is high.
Keywords: African Research